Preserving the Intangible: Orthodox Christian Approaches to Spiritual Heritage - Antohin, Alexandra S. (Religions, 2019)
This article presents the ways Orthodox countries form their own discourses for heritage representation and observes how these practices interact with emerging tourism and preservation agendas. Recent history of heritage tourism in Russia and Ethiopia provides insights into how participants engage with the spiritual heritage of their Churches and the contemporary dilemmas produced when orienting towards preservation protocols that seek to safeguard heritage and make it palatable to a global audience. The Ethiopian case study of Meskel, the festival of the Finding of the True Cross, a UNESCO (United Nations Educational Scientific and Cultural Organization) intangible cultural heritage entry in 2014, is examined in order to identify key issues when spiritual heritage is situated in preservation management discourse. The discussion concludes by considering a vital component of preservation efforts contained within Orthodox Churches and proposes that indigenous approaches to the elaboration and circulation of cultural values be an essential component of heritage policies.